Mutation in IFT80 in a fetus with the phenotype of Verma-Naumoff provides molecular evidence for Jeune-Verma-Naumoff dysplasia spectrum. Issue 2 (30th July 2009) - Cavalcanti, Denise P; Huber, Celine; Le Quan Sang, Kim-Hanh; Baujat, Geneviève; Collins, Felicity; Delezoide, Anne-Lise; Dagoneau, Nathalie; Le Merrer, Martine; Martinovic, Jelena; Mello, Marcos Fernando S; Vekemans, Michel; Munnich, Arnold; et al.
Abstract : Background: The lethal group of short-rib polydactyly (SRP) includes type I (Saldino-Noonan; MIM 263530), type II (Majewski; MIM 263520), type III (Verma-Naumoff; MIM 263510) and type IV (Beemer-Langer; MIM 269860). Jeune and Ellis-van Creveld dysplasias also used to be classified in the SRP group. Recently, mutations in a gene encoding a protein involved in intraflagellar transport, IFT80, have been identified in 3/39 patients with Jeune dysplasia but no extraskeletal manifestation. Methods: Because of clinical and radiological similarities between Jeune dysplasia and the other lethal types of SRP, the authors decided to investigate IFT80 in a cohort of fetuses with the lethal forms of SRP (Majewski, Verma-Naumoff and Beemer-Langer) and antenatally diagnosed cases of Jeune dysplasia. Fifteen fetuses were identified. A double-molecular approach was adopted. For consanguineous families and for those with recurrent sibs, a haplotype analysis around the gene locus was first performed, and, for the others, all the coding exons of IFT80 were directly sequenced. Results: Using the haplotype approach for two families, the authors excluded the IFT80 region as a candidate for them. Direct sequencing of IFT80 in the other 13 cases showed a G-to-C transversion in exon 8 (G241R) in only one SRP case closely related to the type III phenotype. Conclusions: The findings show that mutations in IFT80 can also be responsible for a lethal form of SRP and provide the molecular basis for the Jeune-Verma-Naumoff dysplasia spectrum.